Estudo comparativo de dois conversores Boost quadrático com comutação suave monochaveados para aplicação de rastreamento de máxima potência em sistemas fotovoltaicos - Vilefort, Leandro Sousa (2016)
This paper makes a comparative study of two Soft Single Switched Quadratic Boost Converters (SSS1 and SSS2) focused on Maximum Power Point Tracking (MPPT) of a PV array using Perturb and Observe (P&O) algorithm. The proposed converters maintain the static gain characteristics and dynamics of the original converter with the advantage of considerably reducing the switching losses and Electromagnetic Interference (EMI). It is displayed the input voltage Quadratic Boost converter modeling; qualitative and quantitative analysis of soft switching converters, defining the operation principles, main waveforms, time intervals and the state variables in each operation steps, phase planes of resonant elements, static voltage gain expressions, analysis of voltage and current efforts in semiconductors and the operational curves at 200 W to 800 W. There are presented project of PI, PID and PID + Notch compensators for MPPT closed-loop system and resonant elements design. In order to analyze the operation of a complete photovoltaic system connected to the grid, it was chosen to simulate a three-phase inverter using the P-Q control theory of three-phase instantaneous power. Finally, the simulation results and experimental with the necessary comparative analysis of the proposed converters will be presented.